Preparation method of nano iron aluminate cement
By preparing nanoferroaluminate cement, using ultrafine fly ash and hydrogen oxide surface treatment technology, the problem of slow hydration speed of ferroaluminate cement and easy agglomeration of nano-scale particles is solved, and the effect of improving hydration speed and early strength is achieved.
Patent Information
- Application Number
- CN202411847269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The hydration rate of ferroalaluminate cement is slow, which affects early strength development, and nano-scale cement particles are prone to agglomeration, affecting the hydration rate.
Nanoferroaluminate cement was prepared by mixing aluminum nitrate, red mud, clay and foaming agent and sintering to obtain a nanopowder, which was then mixed with reinforcement filler and dispersant and dried. The reinforcement filler consists of ultrafine fly ash undergoing hydrogen oxide surface treatment, reaction of calcium nitrate with urea, glucose carbonization and polydopamine-modified potassium titanate whiskers.
The hydration speed and early strength of ferroalaluminate cement are improved, the mechanical properties of the hydration products are enhanced, the agglomeration of nano-scale particles is avoided, and the microstructure and durability of the cement are improved.
Smart Images

Figure BDA0005189574310000171 
Figure BDA0005189574310000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferroaluminate cement processing, in particular to a method for preparing nano ferroaluminate cement. Background Art
[0002] Ferroaluminate cement is made by sintering raw materials containing iron and aluminum (such as phosphogypsum) and pyrite slag at high temperature to obtain clinker, and then grinding it with a ball mill. Ferroaluminate cement has good hydration properties and can ensure long-term continuous growth in strength. It can also be used as an admixture to enhance the toughness of concrete and prevent cracking and damage caused by hardening and shrinkage of ordinary silicate concrete. In addition, it also has good performance in resistance to sulfate corrosion and complex salt erosion. Therefore, ferroaluminate cement has a high use value as a concrete raw material.
[0003] The hydration rate of alumina ferrocement is slow, which affects the early strength development of alumina ferrocement. The shrinkage of alumina ferrocement during the solidification process leads to a large number of voids, cracks and fissures in the alumina ferrocement, which affects the tensile strength, toughness and crack resistance of the alumina ferrocement. Grinding alumina ferrocement to nanometer level increases the specific surface area, improves the hydration rate of alumina ferrocement, and enhances the early strength of alumina ferrocement. However, nanometer-level particles are easy to agglomerate, which affects the hydration rate of cement. Summary of the invention
[0004] The invention provides a method for preparing nano-alumina ferrocement, which solves the problems of slow hydration rate of alumina ferrocement and easy agglomeration of nano-scale cement particles.
[0005] The technical solution of the present invention:
[0006] A method for preparing nano-alumina ferrocement comprises the following steps:
[0007] S1. Mix aluminum nitrate, red mud, clay and a foaming agent, and stir at 300-400 r / min for 20-30 min to obtain a mixture;
[0008] S2. Sinter the mixture at 700-850° C. for 30-40 min, cool it to room temperature, take it out, grind it, and obtain nano powder.
[0009] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 500-600 r / min for 30-40 min, and dry to obtain nano ferroaluminate cement.
[0010] The reinforcing filler is prepared by subjecting ultrafine fly ash to surface treatment with hydrogen oxide, mixing with calcium nitrate and urea for reaction, mixing with glucose for carbonization, and finally mixing with potassium titanate whiskers surface-modified with polydopamine.
[0011] Furthermore, the mass ratio of aluminum nitrate, red mud, clay and foaming agent is (8-10):(10-15):(12-15):(80-100).
[0012] Furthermore, the mass ratio of nano powder, reinforcing filler and dispersant is (20-30):(2-5):(3-5).
[0013] Furthermore, the particle size of the nano powder is 300-500nm.
[0014] Furthermore, the foaming agent is urea.
[0015] Furthermore, the dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of (1.2-1.3):(45-55).
[0016] Furthermore, the reinforcing filler is specifically prepared by the following steps:
[0017] A1. After the fly ash is dried, place it in a ball mill, add steel ball media, grind for 1-2 hours, and sieve to obtain ultrafine fly ash.
[0018] A2. Add the ultrafine fly ash to a 15-20% mass fraction of hydrogen peroxide solution, stir at 75-85 ° C for 2-4h, filter, wash and dry to obtain pretreated ultrafine coal powder;
[0019] A3. Calcium nitrate, ethylenediaminetetraacetic acid, sodium hydroxide, sodium dodecyl sulfate and urea are added to deionized water, stirred at 30-40°C until completely dissolved, the pretreated ultrafine coal powder is added, stirring is continued for 15-25min, the temperature is raised to 140-160°C, the reaction is stirred for 8-12h, cooled to room temperature, filtered, washed and dried to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0020] A4. The ultrafine fly ash loaded with nano-calcium carbonate, citric acid and glucose were added to ethanol, stirred evenly, hydrochloric acid was added, and the reaction was stirred. After completion, it was filtered, washed, dried, placed in a tube furnace, and a potassium hydroxide solution with a mass fraction of 20-25% was added. Nitrogen was introduced and carbonized at 750-850 ° C for 2-4h, cooled to room temperature, taken out, washed, and dried to obtain modified ultrafine fly ash;
[0021] A5. Add potassium titanate whiskers to Tris-HCl buffer, stir evenly, add dopamine, stir for 3-5h, filter, wash and dry to obtain polydopamine-modified potassium titanate whiskers;
[0022] A6. Add polydopamine-modified potassium titanate whiskers and modified ultrafine fly ash into deionized water, stir evenly, let stand for 8-12 minutes, filter, wash and dry to obtain a reinforcing filler.
[0023] Furthermore, during the above-mentioned reaction process A1, the fly ash is mixed with the steel ball medium and ground to form ultrafine fly ash with a size of 3.7-6.5 μm.
[0024] Furthermore, in the above-mentioned reaction process A2, hydrogen peroxide has a strong oxidizing property and can react with impurities on the surface of ultrafine fly ash to remove surface impurities and introduce more oxygen-containing functional groups to improve the activity of ultrafine fly ash, which is beneficial to the synthesis of nano-calcium carbonate in the pores and surface of ultrafine coal powder.
[0025] Furthermore, during the above-mentioned reaction A3, the oxygen-containing functional groups contained on the surface of the pretreated ultrafine coal powder can combine with the calcium ions in the calcium nitrate, so that the calcium ions are deposited on the surface of the pretreated ultrafine coal powder. Ethylenediaminetetraacetic acid and sodium dodecyl sulfate serve as surfactants, which can control the release rate of calcium ions in the calcium nitrate, which is conducive to the formation of nano-sized calcium carbonate particles. Urea serves as a chelating agent, and the carbonate ions provided can combine with the calcium ions deposited on the surface of the pretreated ultrafine coal powder to form a calcium carbonate complex. As the hydrothermal reaction proceeds, the calcium carbonate crystals grow, and nano-calcium carbonate with a size of 20-50 nm is formed on the surface of the pretreated ultrafine coal powder, forming ultrafine fly ash loaded with nano-calcium carbonate.
[0026] Furthermore, in the above-mentioned A4 reaction process, citric acid, as a linker, can be combined with the oxygen-containing functional groups in the ultrafine fly ash loaded with nano-calcium carbonate and glucose through chemical bonds, so that the glucose is coated on the surface of the ultrafine fly ash loaded with nano-calcium carbonate. After high-temperature carbonization, the glucose is decomposed by heat to form a dense carbon layer, and the activator potassium hydroxide molecules are decomposed to form pores on the surface of the dense carbon layer, thereby realizing the synthesis of porous carbon on the surface of the ultrafine fly ash loaded with nano-calcium carbonate to form modified ultrafine fly ash.
[0027] Furthermore, during the above reaction A5, in the Tris-HCl buffer, dopamine can self-polymerize on the surface of potassium titanate whiskers to form polydopamine, so that the potassium titanate whiskers have better adhesion, which is conducive to the adhesion of modified ultrafine fly ash on the surface of potassium titanate whiskers.
[0028] Furthermore, during the A6 reaction, the polydopamine layer on the surface of the polydopamine-modified potassium titanate whisker has good adhesion and contains a large amount of phenolic hydroxyl groups, thereby being able to adhere the modified ultrafine fly ash to the surface of the polydopamine-modified potassium titanate whisker to form a reinforcing filler.
[0029] Furthermore, in step A1, the mass ratio of the dried fly ash to the steel ball medium is (5-7):(15-25).
[0030] Furthermore, in step A2, the ratio of the ultrafine fly ash to the hydrogen peroxide solution is (3-5) g: (35-45) mL.
[0031] Furthermore, in step A3, the amount ratio of calcium nitrate, ethylenediaminetetraacetic acid, sodium hydroxide, sodium dodecyl sulfate, urea, deionized water and pretreated ultrafine coal powder is (5-6) g: (0.3-0.7) g: (0.1-0.3) g: (0.2-0.4) g: (5-5.4) g: (60-80) mL: (7-8) g.
[0032] Furthermore, in step A4, the dosage ratio of the ultrafine fly ash loaded with nano-calcium carbonate, citric acid, glucose, ethanol, hydrochloric acid and potassium hydroxide solution is (5-6) g: (0.2-0.3) g: (4-5) g: (45-55) mL: (0.4-0.6) mL: (4-6) mL.
[0033] Furthermore, in step A5, the ratio of the potassium titanate whisker, Tris-HCl buffer and dopamine is (1-2) g: (50-60) mL: (0.6-0.8) g.
[0034] Furthermore, in step A6, the dosage ratio of the polydopamine modified potassium titanate whiskers, modified ultrafine fly ash and deionized water is (1-2) g: (1.3-1.5) g: (25-35) mL.
[0035] Furthermore, the fly ash particle size is 50-60 μm.
[0036] Furthermore, the potassium titanate whisker has a length of 2-5 μm and a diameter of 50-100 nm.
[0037] The present invention has the following beneficial effects:
[0038] (1) In the technical solution of the present invention, the ultrafine fly ash can be filled into the pores generated during the hydration of ferroaluminate cement to improve the mechanical strength of ferroaluminate cement, and the active silicon-alumina substances in the ultrafine fly ash can react with the hydration product Ca(OH) 2 A gelling reaction occurs to generate CSH and CAH gels, thereby increasing the strength of the hydration products of nano-alumina ferroferrate cement; surface treatment of ultrafine fly ash with hydrogen peroxide can remove impurities on the surface of the ultrafine fly ash, and introduce more oxygen-containing functional groups to increase the activity of the ultrafine fly ash, which is beneficial to the synthesis of nano-calcium carbonate in the pores and surface of the ultrafine coal powder.
[0039] (2) In the technical solution of the present invention, nano-calcium carbonate is formed on the surface of ultrafine fly ash. On the one hand, the small-sized nano-calcium carbonate can refine the pores of the ultrafine fly ash and increase the porosity, which is beneficial to absorb water and increase the hydration reaction rate of nano-ferroaluminate cement. On the other hand, the formed nano-calcium carbonate has high mechanical strength and cooperates with the ultrafine fly ash to enhance the mechanical properties of the nano-ferroaluminate cement after hydration. Porous carbon is synthesized on the surface of the modified ultrafine fly ash. The synthesized porous carbon has high adsorption performance and can adsorb and fix metal impurities in the ultrafine fly ash to prevent the metal impurities in the ultrafine fly ash from falling off and affecting the mechanical properties of the hydration product of the nano-ferroaluminate cement. The synthesized porous carbon has high water absorption performance, thereby accelerating the hydration rate of the nano-ferroaluminate cement.
[0040] (3) In the technical scheme of the present invention, the modified ultrafine fly ash is adhered to the surface of the polydopamine modified potassium titanate whisker. On the one hand, the roughness of the surface of the polydopamine modified potassium titanate whisker is increased, thereby increasing the binding force between the polydopamine modified potassium titanate whisker and the nano-alumina ferrocement particles, so that the reinforcing filler has better dispersibility and stability in the nano-alumina ferrocement, effectively improving the microstructure of the nano-alumina ferrocement particles, and improving their durability, compressive strength and flexural strength. On the other hand, the potassium titanate whisker has an excellent aspect ratio and is randomly distributed in the nano-alumina ferrocement, and is then coated on the surface of the nano-alumina ferrocement particles, increasing the steric hindrance of the nano-alumina ferrocement particles, avoiding the agglomeration of the nano-alumina ferrocement particles, resulting in a slow hydration rate and affecting the performance of the nano-alumina ferrocement.
[0041] (4) In the technical solution of the present invention, nano-scale ferroaluminate cement is prepared, which can increase the hydration rate of ferroaluminate cement and form hydration products with higher mechanical properties. Along with the hydration of ferroaluminate cement, reinforcing materials are filled into the gaps of cement hydration products, thereby improving the mechanical properties of nano-ferroaluminate cement slurry. DETAILED DESCRIPTION
[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0044] The red mud particle size was 5.5 mm and was purchased from Shandong Aluminum Co., Ltd.
[0045] The clay particle size was 2-5 μm and was purchased from Beijing Taolesi Handicraft Materials Co., Ltd.
[0046] The fly ash particle size was 50-60 μm and was purchased from Tongyi Energy (Sheyang) Thermal Power Co., Ltd.
[0047] PM2L planetary ball mill, Nanjing Shunchi Technology Development Co., Ltd.
[0048] The particle size of the steel ball medium is 1 mm.
[0049] The mortar item number is T-040001-5, from Shanghai Heqi Glass Instrument Co., Ltd.
[0050] The potassium titanate whiskers are 3 μm in length and 80 nm in diameter.
[0051] The foaming agent is urea.
[0052] Example 1
[0053] A method for preparing nano-alumina ferrocement comprises the following steps:
[0054] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 300 r / min for 20 min to obtain a mixture;
[0055] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 8:10:12:80;
[0056] S2. The mixture is placed in a sintering furnace, sintered at 700° C. for 30 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 300 nm.
[0057] S3. Mix the nano powder, reinforcing filler and dispersant, stir and mix at 500 r / min for 30 min, and dry to obtain nano ferroaluminate cement.
[0058] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 20:2:3.
[0059] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.2:45.
[0060] The reinforcing filler is specifically prepared by the following steps:
[0061] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 5 g of the dried fly ash in a PM2L planetary ball mill, add 15 g of steel ball media, grind for 1 hour, and pass through a 2500 mesh sieve to obtain ultrafine fly ash.
[0062] A2. 3 g of ultrafine fly ash was added to 35 mL of 15% hydrogen peroxide solution, stirred at 75 ° C for 2 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0063] A3. 5 g of calcium nitrate, 0.3 g of ethylenediaminetetraacetic acid, 0.1 g of sodium hydroxide, 0.2 g of sodium dodecyl sulfate and 5 g of urea were added to 60 mL of deionized water, stirred at 30 ° C until completely dissolved, 7 g of pretreated ultrafine coal powder was added, stirring was continued for 15 min, the temperature was raised to 140 ° C, the reaction was stirred for 8 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0064] A4. 5 g of ultrafine fly ash loaded with nano-calcium carbonate, 0.2 g of citric acid and 4 g of glucose were added to 45 mL of ethanol, stirred evenly, 0.4 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, added 6 mL of 20% potassium hydroxide solution by mass, introduced nitrogen, carbonized at 750 ° C for 2 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0065] A5. Add 1 g potassium titanate whisker to 50 mL Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.6 g dopamine, stir for 3 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified potassium titanate whiskers;
[0066] A6. Add 1 g of polydopamine-modified potassium titanate whiskers and 1.3 g of modified ultrafine fly ash into 25 mL of deionized water, stir evenly, let stand for 8 min, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 min to obtain a reinforced filler.
[0067] Example 2
[0068] A method for preparing nano-alumina ferrocement comprises the following steps:
[0069] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 350 r / min for 25 min to obtain a mixture;
[0070] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 9:13:14:90;
[0071] S2. The mixture is placed in a sintering furnace, sintered at 800° C. for 35 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 400 nm.
[0072] S3. Mix the nano powder, reinforcing filler and dispersant, stir and mix at 550 r / min for 35 min, and dry to obtain nano ferroaluminate cement.
[0073] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 25:3:4.
[0074] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.25:50.
[0075] The reinforcing filler is specifically prepared by the following steps:
[0076] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 6 g of the dried fly ash in a PM2L planetary ball mill, add 20 g of steel ball media, grind for 1.5 hours, and pass through a 2500 mesh sieve to obtain ultrafine fly ash.
[0077] A2. 4 g of ultrafine fly ash was added to 40 mL of 18% hydrogen peroxide solution, stirred at 80 ° C for 3 h, filtered, washed with deionized water 3 times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0078] A3. 5.5 g of calcium nitrate, 0.5 g of ethylenediaminetetraacetic acid, 0.2 g of sodium hydroxide, 0.3 g of sodium dodecyl sulfate and 5.2 g of urea were added to 70 mL of deionized water, stirred at 35 ° C until completely dissolved, 7.5 g of pretreated ultrafine coal powder was added, stirring was continued for 20 min, the temperature was raised to 150 ° C, the reaction was stirred for 10 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0079] A4. 5.5 g of ultrafine fly ash loaded with nano-calcium carbonate, 0.25 g of citric acid and 4.5 g of glucose were added to 50 mL of ethanol, stirred evenly, 0.5 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, 5 mL of 23% potassium hydroxide solution was added, nitrogen was introduced, carbonized at 800 ° C for 3 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0080] A5. Add 1.5 g potassium titanate whiskers to 55 mL Tris-HCl buffer at pH 8.5, stir evenly, add 0.7 g dopamine, stir for 4 h, filter, wash with deionized water three times, and dry in an oven at 70 °C for 10 min to obtain polydopamine-modified potassium titanate whiskers;
[0081] A6. Add 1.5 g of polydopamine-modified potassium titanate whiskers and 1.4 g of modified ultrafine fly ash into 30 mL of deionized water, stir evenly, let stand for 10 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a reinforced filler.
[0082] Example 3
[0083] A method for preparing nano-alumina ferrocement comprises the following steps:
[0084] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 400 r / min for 30 min to obtain a mixture;
[0085] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 10:15:15:100;
[0086] S2. The mixture is placed in a sintering furnace, sintered at 850° C. for 40 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 500 nm.
[0087] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 600 r / min for 40 min, and dry to obtain nano ferroaluminate cement.
[0088] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 30:5:5.
[0089] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.3:55.
[0090] The reinforcing filler is specifically prepared by the following steps:
[0091] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 7g of the dried fly ash in a PM2L planetary ball mill, add 25g of steel ball media, grind for 2 hours, and pass through a 2500-mesh sieve to obtain ultrafine fly ash.
[0092] A2. 5 g of ultrafine fly ash was added to 45 mL of a 20% hydrogen peroxide solution, stirred at 85 ° C for 4 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0093] A3. 6 g of calcium nitrate, 0.7 g of ethylenediaminetetraacetic acid, 0.3 g of sodium hydroxide, 0.4 g of sodium dodecyl sulfate and 5.4 g of urea were added to 80 mL of deionized water, stirred at 40 ° C until completely dissolved, 8 g of pretreated ultrafine coal powder was added, stirring was continued for 25 min, the temperature was raised to 160 ° C, the reaction was stirred for 12 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0094] A4. 6 g of ultrafine fly ash loaded with nano-calcium carbonate, 0.3 g of citric acid and 5 g of glucose were added to 55 mL of ethanol, stirred evenly, 0.6 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, 6 mL of 25% potassium hydroxide solution was added, nitrogen was introduced, carbonized at 850 ° C for 4 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0095] A5. Add 2 g potassium titanate whiskers to 60 mL Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g dopamine, stir for 5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified potassium titanate whiskers;
[0096] A6. Add 2 g of polydopamine-modified potassium titanate whiskers and 1.5 g of modified ultrafine fly ash into 35 mL of deionized water, stir evenly, let stand for 12 min, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain a reinforced filler.
[0097] Comparative Example 1
[0098] A method for preparing nano-alumina ferrocement comprises the following steps:
[0099] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 400 r / min for 30 min to obtain a mixture;
[0100] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 10:15:15:100;
[0101] S2. The mixture is placed in a sintering furnace, sintered at 850° C. for 40 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 500 nm.
[0102] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 600 r / min for 40 min, and dry to obtain nano ferroaluminate cement.
[0103] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 30:5:5.
[0104] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.3:55.
[0105] The reinforcing filler is specifically prepared by the following steps:
[0106] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 7g of the dried fly ash in a PM2L planetary ball mill, add 25g of steel ball media, grind for 2 hours, and pass through a 2500-mesh sieve to obtain ultrafine fly ash.
[0107] A2. 6 g of calcium nitrate, 0.7 g of ethylenediaminetetraacetic acid, 0.3 g of sodium hydroxide, 0.4 g of sodium dodecyl sulfate and 5.4 g of urea were added to 80 mL of deionized water, stirred at 40 ° C until completely dissolved, 8 g of ultrafine fly ash was added, stirring was continued for 25 min, the temperature was raised to 160 ° C, the reaction was stirred for 12 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0108] A3. 6 g of ultrafine fly ash loaded with nano-calcium carbonate, 0.3 g of citric acid and 5 g of glucose were added to 55 mL of ethanol, stirred evenly, 0.6 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, 6 mL of 25% potassium hydroxide solution was added, nitrogen was introduced, carbonized at 850 ° C for 4 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0109] A4. Add 2 g potassium titanate whiskers to 60 mL Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g dopamine, stir for 5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified potassium titanate whiskers;
[0110] A5. Add 2 g of polydopamine-modified potassium titanate whiskers and 1.5 g of modified ultrafine fly ash into 35 mL of deionized water, stir evenly, let stand for 12 min, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain a reinforced filler.
[0111] Comparative Example 2
[0112] A method for preparing nano-alumina ferrocement comprises the following steps:
[0113] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 400 r / min for 30 min to obtain a mixture;
[0114] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 10:15:15:100;
[0115] S2. The mixture is placed in a sintering furnace, sintered at 850° C. for 40 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 500 nm.
[0116] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 600 r / min for 40 min, and dry to obtain nano ferroaluminate cement.
[0117] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 30:5:5.
[0118] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.3:55.
[0119] The reinforcing filler is specifically prepared by the following steps:
[0120] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 7g of the dried fly ash in a PM2L planetary ball mill, add 25g of steel ball media, grind for 2 hours, and pass through a 2500-mesh sieve to obtain ultrafine fly ash.
[0121] A2. 5 g of ultrafine fly ash was added to 45 mL of a 20% hydrogen peroxide solution, stirred at 85 ° C for 4 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0122] A3. 6 g of pretreated ultrafine coal powder, 0.3 g of citric acid and 5 g of glucose were added to 55 mL of ethanol, stirred evenly, 0.6 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, 6 mL of 25% potassium hydroxide solution was added, nitrogen was introduced, carbonized at 850 ° C for 4 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0123] A4. Add 2 g potassium titanate whiskers to 60 mL Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g dopamine, stir for 5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified potassium titanate whiskers;
[0124] A5. Add 2 g of polydopamine-modified potassium titanate whiskers and 1.5 g of modified ultrafine fly ash into 35 mL of deionized water, stir evenly, let stand for 12 min, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain a reinforced filler.
[0125] Comparative Example 3
[0126] A method for preparing nano-alumina ferrocement comprises the following steps:
[0127] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 400 r / min for 30 min to obtain a mixture;
[0128] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 10:15:15:100;
[0129] S2. The mixture is placed in a sintering furnace, sintered at 850° C. for 40 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 500 nm.
[0130] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 600 r / min for 40 min, and dry to obtain nano ferroaluminate cement.
[0131] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 30:5:5.
[0132] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.3:55.
[0133] The reinforcing filler is specifically prepared by the following steps:
[0134] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 7g of the dried fly ash in a PM2L planetary ball mill, add 25g of steel ball media, grind for 2 hours, and pass through a 2500-mesh sieve to obtain ultrafine fly ash.
[0135] A2. 5 g of ultrafine fly ash was added to 45 mL of a 20% hydrogen peroxide solution, stirred at 85 ° C for 4 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0136] A3. 6 g of calcium nitrate, 0.7 g of ethylenediaminetetraacetic acid, 0.3 g of sodium hydroxide, 0.4 g of sodium dodecyl sulfate and 5.4 g of urea were added to 80 mL of deionized water, stirred at 40 ° C until completely dissolved, 8 g of pretreated ultrafine coal powder was added, stirring was continued for 25 min, the temperature was raised to 160 ° C, the reaction was stirred for 12 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0137] A4. Add 2 g potassium titanate whiskers to 60 mL Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.8 g dopamine, stir for 5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified potassium titanate whiskers;
[0138] A5. Add 2 g of polydopamine-modified potassium titanate whiskers and 1.5 g of ultrafine fly ash loaded with nano-calcium carbonate into 35 mL of deionized water, stir evenly, let stand for 12 min, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 min to obtain a reinforced filler.
[0139] Comparative Example 4
[0140] A method for preparing nano-alumina ferrocement comprises the following steps:
[0141] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 400 r / min for 30 min to obtain a mixture;
[0142] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 10:15:15:100;
[0143] S2. The mixture is placed in a sintering furnace, sintered at 850° C. for 40 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 500 nm.
[0144] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 600 r / min for 40 min, and dry to obtain nano ferroaluminate cement.
[0145] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 30:5:5.
[0146] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.3:55.
[0147] The reinforcing filler is specifically prepared by the following steps:
[0148] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 7g of the dried fly ash in a PM2L planetary ball mill, add 25g of steel ball media, grind for 2 hours, and pass through a 2500-mesh sieve to obtain ultrafine fly ash.
[0149] A2. 5 g of ultrafine fly ash was added to 45 mL of a 20% hydrogen peroxide solution, stirred at 85 ° C for 4 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0150] A3. 6 g of calcium nitrate, 0.7 g of ethylenediaminetetraacetic acid, 0.3 g of sodium hydroxide, 0.4 g of sodium dodecyl sulfate and 5.4 g of urea were added to 80 mL of deionized water, stirred at 40 ° C until completely dissolved, 8 g of pretreated ultrafine coal powder was added, stirring was continued for 25 min, the temperature was raised to 160 ° C, the reaction was stirred for 12 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0151] A4. 6 g of ultrafine fly ash loaded with nano-calcium carbonate, 0.3 g of citric acid and 5 g of glucose were added to 55 mL of ethanol, stirred evenly, 0.6 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, 6 mL of 25% potassium hydroxide solution was added, nitrogen was introduced, carbonized at 850 ° C for 4 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0152] A5. Add 2 g potassium titanate whisker and 1.5 g modified ultrafine fly ash into 35 mL deionized water, stir evenly, let stand for 12 min, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain a reinforcing filler.
[0153] Comparative Example 5
[0154] A method for preparing nano-alumina ferrocement comprises the following steps:
[0155] S1. Mix aluminum nitrate, red mud, clay and urea, and stir at 400 r / min for 30 min to obtain a mixture;
[0156] Among them, the mass ratio of aluminum nitrate, red mud, clay and urea is 10:15:15:100;
[0157] S2. The mixture is placed in a sintering furnace, sintered at 850° C. for 40 minutes, cooled to room temperature, taken out, and ground in a mortar to obtain nanopowder, wherein the particle size of the nanopowder is 500 nm.
[0158] S3. Mix the nano powder, reinforcing filler and dispersant, stir at 600 r / min for 40 min, and dry to obtain nano ferroaluminate cement.
[0159] Among them, the mass ratio of nano powder, reinforcing filler and dispersant is 30:5:5.
[0160] The dispersant is a sodium carboxymethyl cellulose solution, which is prepared by mixing sodium carboxymethyl cellulose and deionized water in a mass ratio of 1.3:55.
[0161] The reinforcing filler is specifically prepared by the following steps:
[0162] A1. Dry the fly ash in an oven at 105°C for 2 hours, place 7g of the dried fly ash in a PM2L planetary ball mill, add 25g of steel ball media, grind for 2 hours, and pass through a 2500-mesh sieve to obtain ultrafine fly ash.
[0163] A2. 5 g of ultrafine fly ash was added to 45 mL of a 20% hydrogen peroxide solution, stirred at 85 ° C for 4 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain pretreated ultrafine coal powder;
[0164] A3. 6 g of calcium nitrate, 0.7 g of ethylenediaminetetraacetic acid, 0.3 g of sodium hydroxide, 0.4 g of sodium dodecyl sulfate and 5.4 g of urea were added to 80 mL of deionized water, stirred at 40 ° C until completely dissolved, 8 g of pretreated ultrafine coal powder was added, stirring was continued for 25 min, the temperature was raised to 160 ° C, the reaction was stirred for 12 h, cooled to room temperature, filtered, washed with deionized water 5 times, and dried in an oven at 80 ° C for 10 min to obtain ultrafine fly ash loaded with nano-calcium carbonate;
[0165] A4. 6 g of ultrafine fly ash loaded with nano-calcium carbonate, 0.3 g of citric acid and 5 g of glucose were added to 55 mL of ethanol, stirred evenly, 0.6 mL of 36% hydrochloric acid was added, stirred and reacted at 70 ° C for 30 min, filtered, washed with deionized water 3 times, dried in an oven at 80 ° C for 10 min, placed in a tube furnace, 6 mL of 25% potassium hydroxide solution was added, nitrogen was introduced, carbonized at 850 ° C for 4 h, cooled to room temperature, taken out, washed with deionized water until the washing liquid was neutral, and dried in an oven at 70 ° C for 10 min to obtain modified ultrafine fly ash;
[0166] A5. Add 2 g of nano-alumina to 60 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.8 g of dopamine, stir for 5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified nano-alumina;
[0167] A6. Add 2 g of polydopamine-modified nano-alumina and 1.5 g of modified ultrafine fly ash into 35 mL of deionized water, stir evenly, let stand for 12 min, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain a reinforced filler.
[0168] The performance of the nano-alumina ferrocement prepared in Examples 1-3 and Comparative Examples 1-5 is now tested.
[0169] Setting time test: The setting time of the nano-alumina ferroaluminate cement prepared above was tested according to GB / T1346-2011 “Test methods for water consumption, setting time and stability of cement of standard consistency”.
[0170] Cement hydration heat test: The hydration heat of the nano-alumina ferroaluminate cement prepared above was tested according to the standard GB / T12959-2008 "Method for determination of cement hydration heat".
[0171] Flexural strength and compressive strength test: The flexural strength and compressive strength of the nano-alumina ferroaluminate cement prepared above were tested according to the JC / T933-2019 "Rapid Hardening High-Iron Sulphoaluminate Cement" standard; as shown in Table 1 below.
[0172] Table 1 Performance test of nano-alumina ferrocement prepared in Examples 1-3 and Comparative Examples 1-5
[0173]
[0174]
[0175] It can be seen from the data in Table 1 that the nano-alumina-ferrocement prepared in Examples 1-3 has an excellent hydration rate, and the mechanical strength of the hydration product is good. In Comparative Example 1, the pre-treated ultrafine coal powder is replaced with a reinforcing filler prepared from ultrafine coal powder and added to the nano-alumina-ferrocement, and its hydration degree and mechanical strength decrease, proving that the surface treatment of ultrafine fly ash with hydrogen peroxide improves the activity of ultrafine fly ash, is conducive to the gelling reaction of ultrafine fly ash with the hydration product of alumina-ferrocement, improves the strength, and is conducive to the synthesis of nano calcium carbonate in the pores and surface of ultrafine coal powder.
[0176] In Comparative Example 2, the ultrafine fly ash loaded with nano-calcium carbonate was replaced with a reinforcing filler prepared by pre-treating ultrafine coal powder and added to the nano-alumina ferrocement. Its hydration degree and mechanical strength decreased, proving that nano-calcium carbonate was formed on the surface of the ultrafine fly ash, which refined the pores of the ultrafine fly ash and increased the porosity, which was conducive to absorbing moisture, increasing the hydration reaction rate of the nano-alumina ferrocement, and enhancing the mechanical strength of the cement hydration product.
[0177] In Comparative Example 3, the modified ultrafine fly ash is replaced with a reinforcing filler prepared by ultrafine fly ash loaded with nano-calcium carbonate and added to nano-alumina ferrocement. Its hydration degree and mechanical strength decrease, indicating that the porous carbon synthesized on the surface of the modified ultrafine fly ash can adsorb and fix metal impurities in the ultrafine fly ash, thereby improving the mechanical strength of the cement hydration product. In addition, the synthesized porous carbon has a higher water absorption performance, thereby improving the hydration rate of nano-alumina ferrocement.
[0178] In Comparative Example 4, the reinforcing filler prepared by replacing the polydopamine-modified potassium titanate whiskers with potassium titanate whiskers was added to the nano-alumina ferrocement, and its mechanical strength decreased, proving that the polydopamine-modified potassium titanate whiskers are beneficial to the adhesion of the modified ultrafine fly ash to the surface of the polydopamine-modified potassium titanate whiskers, increasing the surface roughness, improving the binding force with the nano-alumina ferrocement particles, and improving its durability, compressive resistance and flexural strength.
[0179] In Comparative Example 5, reinforcing fillers prepared by replacing nano-alumina with potassium titanate whiskers were added to nano-alumina ferrocement, and its hydration degree and mechanical strength decreased, proving the excellent aspect ratio of potassium titanate whiskers. They were randomly distributed in the nano-alumina ferrocement and then coated on the surface of the nano-alumina ferrocement particles, increasing the steric hindrance of the nano-alumina ferrocement particles and avoiding the agglomeration of the nano-alumina ferrocement particles, resulting in a slower hydration rate and affecting the performance of the nano-alumina ferrocement.
[0180] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0181] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing nano-alumina ferrocement, characterized in that: The method comprises the following preparation steps: S1. Mix aluminum nitrate, red mud, clay and a foaming agent, and stir at 300-400 r / min for 20-30 min to obtain a mixture; S2. Sinter the mixture at 700-850° C. for 30-40 min, cool it to room temperature, take it out, grind it, and obtain nano powder. S3, mixing the nano powder, reinforcing filler and dispersant, stirring at 500-600 r / min for 30-40 min, and drying to obtain nano ferroaluminate cement; The reinforcing filler is prepared by subjecting ultrafine fly ash to surface treatment with hydrogen oxide, mixing with calcium nitrate and urea for reaction, mixing with glucose for carbonization, and finally mixing with potassium titanate whiskers surface-modified with polydopamine.
2. The method for preparing nano-alumina ferrocement according to claim 1, characterized in that: The reinforcing filler is specifically prepared by the following steps: A1. After the fly ash is dried, place the dried fly ash in a ball mill, add steel ball media, grind for 1-2 hours, and sieve to obtain ultrafine fly ash; A2. Add the ultrafine fly ash to a 15-20% mass fraction of hydrogen peroxide solution, stir at 75-85 ° C for 2-4h, filter, wash and dry to obtain pretreated ultrafine coal powder; A3. Calcium nitrate, ethylenediaminetetraacetic acid, sodium hydroxide, sodium dodecyl sulfate and urea are added to deionized water, stirred at 30-40°C until completely dissolved, the pretreated ultrafine coal powder is added, stirring is continued for 15-25min, the temperature is raised to 140-160°C, the reaction is stirred for 8-12h, cooled to room temperature, filtered, washed and dried to obtain ultrafine fly ash loaded with nano-calcium carbonate; A4. The ultrafine fly ash loaded with nano-calcium carbonate, citric acid and glucose were added to ethanol, stirred evenly, hydrochloric acid was added, and the reaction was stirred. After completion, it was filtered, washed, dried, placed in a tube furnace, and a potassium hydroxide solution with a mass fraction of 20-25% was added. Nitrogen was introduced and carbonized at 750-850 ° C for 2-4h, cooled to room temperature, taken out, washed, and dried to obtain modified ultrafine fly ash; A5. Add potassium titanate whiskers to Tris-HCl buffer, stir evenly, add dopamine, stir for 3-5h, filter, wash and dry to obtain polydopamine-modified potassium titanate whiskers; A6. Add polydopamine-modified potassium titanate whiskers and modified ultrafine fly ash into deionized water, stir evenly, let stand for 8-12 minutes, filter, wash and dry to obtain a reinforcing filler.
3. The method for preparing nano-alumina ferrocement according to claim 2, characterized in that: In step A1, the mass ratio of the dried fly ash to the steel ball medium is (5-7):(15-25).
4. The method for preparing nano-alumina ferrocement according to claim 2, characterized in that: In step A2, the ratio of the ultrafine fly ash to the hydrogen peroxide solution is (3-5) g: (35-45) mL.
5. The method for preparing nano-alumina ferrocement according to claim 2, characterized in that: In step A3, the amount ratio of calcium nitrate, ethylenediaminetetraacetic acid, sodium hydroxide, sodium dodecyl sulfate, urea, deionized water and pretreated ultrafine coal powder is (5-6) g: (0.3-0.7) g: (0.1-0.3) g: (0.2-0.4) g: (5-5.4) g: (60-80) mL: (7-8) g.
6. The method for preparing nano-alumina ferrocement according to claim 2, characterized in that: In step A4, the dosage ratio of the ultrafine fly ash loaded with nano-calcium carbonate, citric acid, glucose, ethanol, hydrochloric acid and potassium hydroxide solution is (5-6) g: (0.2-0.3) g: (4-5) g: (45-55) mL: (0.4-0.6) mL: (4-6) mL.
7. The method for preparing nano-alumina ferrocement according to claim 2, characterized in that: In step A5, the ratio of the potassium titanate whisker, Tris-HCl buffer and dopamine is (1-2) g: (50-60) mL: (0.6-0.8) g.
8. The method for preparing nano-alumina ferrocement according to claim 2, characterized in that: In step A6, the dosage ratio of the polydopamine modified potassium titanate whiskers, modified ultrafine fly ash and deionized water is (1-2) g: (1.3-1.5) g: (25-35) mL.